Toxicological asessment of a dietary supplement based on erbium and europium chlorides by intragastric administration to white rats - Vlasenko, Evgenii K.; Yuvs, George V.; Rybina, Tatyana N.; Klimovich, Olga M.; Berdina, Elena L.; Stelmakh, Victor A.; Sysa, Aliaksei G.; Gapanovich, Vladimir N. (Journal of the Belarusian State University. Ecology, 2020)
Acute toxicity of a new dietary supplement based on erbium and europium chlorides by intragastric administration to white rats was studied. The results obtained were as follows:LD50 values were 6864.90 mg/kg in male rats and 5372.01 mg/kg in female rats (VI class of toxicity, relatively harmless). In rats of both sexes at doses of 3000, 4500 and 6000 mg/kg, clinical signs of intoxication were characterized by slow and passive motor activity; at a dose of 1500 mg/kg, symptoms of intoxication were not observed. There were no significant changes in the body weight of animals and its growth under the studied doses. Macroscopic examination of the main organs of life support of rats at doses of 1500, 3000, 4500 and 6000 mg/ kg did not reveal significant deviations in the structure, analysis of their weight coefficients showed a significant increase in the relative weight of the liver: 1.3−1.5 times in male rats, 1.2−1.4 times in female rats, compared to the corresponding control values.
Keywords: erbium; europium; toxicity; dietary supplements; laboratory animals